The Bushland, Texas, maize evapotranspiration, growth, and yield dataset Collection - Steven R. Evett; Gary W. Marek; Paul D. Colaizzi; Karen S. Copeland; Brice B. Ruthardt; Terry A. Howell (Scientific Data)
Abstract A collection of datasets describing six years of experiments on maize (Zea mays, L.) (corn) is presented (1989, 1990, 1994, 2013, 2016, and 2018). Four weighing lysimeters were used to determine crop evapotranspiration (ET). In-soil and above ground microclimate and ET data are presented on a 15-minute interval as are weather data for all days of the year. Data analysis determined ET, precipitation, irrigation, and dew and frost accumulation on a 15-minute basis from lysimeter mass data. Soil water content data from calibrated neutron probe readings is presented on a periodic basis. Crop planting, harvest, fertilization, pest control, and other agronomic information are presented in agronomic calendars by day of year. Crop growth data are presented on a periodic basis throughout the growing season, as are final crop biomass and yield data. The data are suitable for analysis of effects of irrigation and other agronomic decisions on crop yield and water productivity in the Southern High Plains region of the USA, for model calibration and testing, and for model improvement.